Defeat and proficiencies. Issue 1 (20th October 2022) - Kelp, Christoph
Abstract: Virtue epistemology is the view that beliefs are attempts at truth (or perhaps knowledge) and, as a result, can be assessed as successful, competent, and apt. Moreover, virtue epistemology identifies central epistemic properties with normative properties of beliefs as attempts. In particular, knowledge is apt belief and justified belief is competent belief. This paper develops a systematic virtue epistemological account of defeat (of justification/competence). I provide reason to think that defeat occurs not only for beliefs but for attempts more general. The key constructive idea is that defeaters are evidence that attempting (in a certain way) isn't successful and that defeaters defeat the competence of an attempt when one stands in a certain normative relation to the defeater. I argue that while this account handles paradigm cases of defeat both within epistemology and beyond nicely, cases of external (sometimes also 'normative' or 'propositional') defeat continue to cause trouble. To handle these cases, I develop a distinctively functionalist version of virtue epistemology. This functionalist version of virtue epistemology allows me to countenance proficiencies, that is, roughly, abilities that have the function to produce successes under certain conditions. It is the normative import of proficiencies that delivers the normative relation that serves to explain defeat in cases of external defeat. In this way, the functionalist version of virtue epistemology ushers the way towards a satisfactory account even of external defeat.